Lumefantrine co-amorphous systems using deoxycholic acid as a co-former: NIR at-line process monitoring by machine learning - Otsuka, Yuta; Naitou, Kiyotada; Miyata, Takeshi (Bio-medical materials and engineering, 2025)
BackgroundVarious methods have been reported for improving the water-insoluble drugs in oral administration formulations. Among them, amorphization has been attracting attention and developed as a method for solubilizing API (active pharmaceutical ingredient)s by changing their physicochemical properties. Molecular complexation is also known as a method for solubilizing APIs by synthesizing cocrystals, etc. Co-amorphization, which achieves both molecular complexation and amorphization, is effective and has attracted attention. Thus, co-amorphization has been proven to be an effective approach to solubilization.ObjectiveThis study aims to improve the solubility of lumefantrine, used here as a model compound, through co-amorphization with deoxycholic acid.SignificanceThe physicochemical properties are an important factor in developing pharmaceutical ingredients. Hydrogen-bonded co-amorphization has gained attention as a method to enhance the physicochemical properties of hydrophobic drugs.MethodsThe co-amorphous Lumefantrine-deoxycholic acid system was prepared using a mechanochemical synthesis method based on ball milling. The synthesis process was monitored by powder X-ray diffraction and near-infrared spectroscopy. The products and materials were analyzed by thermal analysis.ResultsSpectroscopic analysis revealed that the two molecules were complexed through intermolecular hydrogen bonding interactions. The produced co-amorphous has no melting point was found by thermal analysis.ConclusionsProcess monitoring also indicated the presence of a metastable crystalline Lumefantrine (LMF) intermediate.